Upgrading fair trade: a case study in Madagascar. Issue 3 (3rd April 2021) - Ballet, Jérôme; Gondard-Delcroix, Claire; Cedras, Dilane
ABSTRACT: Fair trade has come under a barrage of criticism in recent years. Often the two targets of this criticism have been the impact of fair trade and the asymmetry of power between the Global North and South that benefits the North. This article presents a case study from Madagascar which illustrates the positive aspects of fair trade, along with its capacity to involve Global South producers higher up the value chain (functional upgrading), thereby ensuring that these producers are better able to manage their production and the inherent risks.